METHODOLOGY OF ORGANIZING AND CONDUCTING MECHANISMS FOR ASSESSMENT OF TEACHERS' PEDAGOGICAL SKILLS IN IMPROVING THE QUALITY OF EDUCATION (TAMADDUN NURI JURNALI, 2024)
This article provides information on the methodology of organizing and conducting mechanisms for evaluating teachers' pedagogical skills in improving the quality of education.